Pengaruh Keamanan Transaksi, Online Costumer Review Dan Rating Terhadap Minat Beli Konsumen Marketplace Tokopedia (Studi Kasus Pada Mahasiswa Di Kota Malang) - Ramdany, Kalfin; Hidayati, Nur; Suharto, M. Khoirul Anwarudin Broto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract  This research aims to analyze the influence of transaction security, online customer reviews and ratings on purchasing interest. This research is a type of quantitative research. The sample in this study was 68 respondents, with sampling using purposing sampling. Based on the research results, it can be concluded that transaction security, while online customer reviews and ratings simultaneously have a significant effect on student purchasing interest in Malang City. Keywords: Transaction Security, Online Customer Review, Rating, and Buying  Interest.